EXPLORING THE STRATEGIC ROLE OF HUMAN RESOURCES DEVELOPMENT IN CAPACITY BUILDING - Khatijatusshalihah, Khatijatusshalihah (Fakultas Psikologi, Universitas Islam Negeri (UIN) Ar Raniry Banda Aceh, 2016)
This paper reviews studies about capacity building that related to Human Resources Development (HRD). Capacity building can also be classified into three levels; individual capacity building, institutional capacity building and systemic capacity building capacity building (Garriga, 2013). McLagan (1989) explained that HRD is a field of study that typically consists of three main practice domains – organization development, training & development, and career development. This study seeks to explore how capacity building has been discussed in the field of HRD along with the challenges faced by HRD professional while implementing capacity building. I summarized the articles based on the their focus, research paradigms, guiding theories, journal publisher and years of publication within the past two decades. This paper also has implications for HRD professionals who are interested in the areas of capacity building.